Spatiotemporal dynamic changes in transpiration in the shoot sheath and its relation to water transportation during rapid growth of Moso bamboo - Li, Juan; Chen, Lei; Wang, Jinge; Xu, Junlei; Zheng, Huifang; Bai, Yucong; Cheng, Zhanchao; Mu, Shaohua; Gao, Jian (Frontiers in Forests and Global Change, 2024)
Transpiration is the driving force of water transport, which plays a crucial role in the rapid growth of bamboo shoots. Nonetheless, the transpiration changes that occur in the shoot sheath of Moso bamboo during the leafless stage and the physiological processes involved in water transport from the mother bamboo to bamboo shoots are not completely understood. Hence, this study investigated the temporal dynamics of the transpiration rate (Tr) and stomatal conductance (gs) of the sheaths from bamboo shoots to culms, and diurnal variations in Tr and gs, as well as the spatial dynamics of Tr and gs in various parts of the shoot sheaths. Water distribution patterns in bamboo shoots were analyzed using the isotope tracer method, and the water transportation path in bamboo shoots was determined by soaking the shoots in fuchsine dye solution. We observed that the Tr was higher in bamboo shoots at heights of 4 m and 7 m compared to that at 0.5 m, 1 m, 2 m, and 13 m, with rates ranging from 6.8 mmol/m 2 /s 1 to 8.3 mmol/m 2 /s. Additionally, the Tr and gs of the shoot sheath were lower at noon, but higher in the morning and evening. The Tr in the lower parts of the culm sheath was higher than that in the upper part (height: 0.5-4 m). However, when injected into the mother bamboo, D2O was not immediately transported to the shoots via the mother culms but was transported upward through the vascular bundle, with a larger vascular bundle near the pulp cavity transporting high volumes of water. These findings provide the foundation for further studies on the rapid growth of Moso bamboo and establish a theoretical basis for water management during its shoot developmental period.